Juridical Analysis Of Legal Protection For Eldery Victims Of Domestic Violence - Irawan, Kaysya Bintang Natalia; Arsawati, Ni Nyoman Juwita (Fakultas Hukum Dehasen, 2025)
This study aims to analyze and examine legal protection for the eldery as victims of domestic violence. The issue focused on in this study is the gap that occurs in legal protection for the eldery as victims of domestic violence, who do not yet have specific regulations. The method used is normative legal research, using a statutory and conceptual approach. The results of the study indicate that there are problems in legal protection for the eldery as victims of domestic violence. Therefore, in the future, it is considered necessary to update the legal framework to provide specific protection, given that the eldery are a vulnerable group to violence, along with children and women.